1997
DOI: 10.1046/j.1365-2125.1997.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Is metronidazole teratogenic? A meta‐analysis

Abstract: Aim In order to assess whether the use of metronidazole during pregnancy is associated with a higher risk of congenital malformations, a meta-analysis was conducted. Methods All epidemiological studies (cohort and case-control) which estimate risk of congenital malformations after exposure to metronidazole during early pregnancy were included in the meta-analysis. To obtain a summary odds ratio, the MantelHaenszel method was used. A test to verify absence of heterogeneity was also performed. Results One unpubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(72 citation statements)
references
References 9 publications
1
67
0
4
Order By: Relevance
“…95 The epidemiological data regarding maternal vaginal metronidazole (FDA category B) use early in pregnancy were summarized in 2 meta-analyses. 96,97 In both instances, the risk of congenital anomalies in offspring was not increased. One of the studies included in these analyses specifically examined a large group (984) of infants with cardiovascular defects.…”
Section: Vitamin a Cogeners/retinoidsmentioning
confidence: 88%
“…95 The epidemiological data regarding maternal vaginal metronidazole (FDA category B) use early in pregnancy were summarized in 2 meta-analyses. 96,97 In both instances, the risk of congenital anomalies in offspring was not increased. One of the studies included in these analyses specifically examined a large group (984) of infants with cardiovascular defects.…”
Section: Vitamin a Cogeners/retinoidsmentioning
confidence: 88%
“…The Food and Drug Administration (FDA) classified metronidazole as a class B risk factor for pregnancy. Accordingly, use of metronidazole for amoebiasis in pregnant women is not currently recommended (58,59), although a causal connection between metronidazole exposure during pregnancy and birth defects has not been established (45,63,94). Emetine and dehydroemetine hydrochloride have serious side effects, including nausea, vomiting, cardiotoxicity, local pain, and tenderness (162).…”
Section: Current Chemotherapeutics Current Chemotherapeutics For E Hmentioning
confidence: 99%
“…36 Multiple studies and meta-analyses have concluded that metronidazole does not appear to be associated with an increased teratogenic risk. [37][38][39] However, two studies have suggested that treatment with metronidazole in women with TV can increase preterm birth. 40,41 This adverse effect has been difficult to explain, but raises a caution about the unnecessary use of metronidazole in pregnancy.…”
Section: Adherence To the Syndromic Management Treatment Guidelinesmentioning
confidence: 99%